Characterization of recombinant human bone morphogenetic protein‐2 delivery from injectable hyaluronan‐based hydrogels by means of 125I‐radiolabelling. (25th August 2012) - Piskounova, Sonya; Gedda, Lars; Hulsart‐Billström, Gry; Hilborn, Jöns; Bowden, Tim
Abstract This study presents a thorough in vitro and in vivo characterization of the delivery of bone morphogenetic protein 2 (BMP‐2) from a hyaluronan‐based hydrogel system. The in vitro release of BMP‐2 from similar hydrogels has previously been studied by enzyme‐linked immunosorbent assay (ELISA), by which only a fraction of the loaded protein is detected. In the current study, 125I radiolabelling was used instead to monitor BMP‐2 in vitro and in vivo. To minimize protein loss during handling, 125I‐BMP‐2 adsorption to different tubes was studied at different times and temperatures. The data showed that Protein LoBind tubes exhibited the lowest protein affinity. Furthermore, a biphasic release profile of biologically active BMP‐2 was observed both in vitro and in vivo, with the initial fast phase during the first week, followed by a slower release during the remaining 3 weeks. The initial fast‐release phase corresponded to the early bone formation observed after 8 days in an ectopic model in rats. Bone volume and mineral content increased until day 14, after which a decrease in bone volume was observed, possibly due to resorption in response to decreased amounts of released BMP‐2. Overall, the results suggested that cautious protein handling and a reliable quantification technique are essential factors for successful design of a BMP‐2 delivery system. Copyright © 2012 John Wiley & Sons, Ltd.